Формування іміджу авторитарного лідера в сучасних умовах - Шурко, О.; Новик, А. (Українська національна ідея: реалії та перспективи розвитку, 2010)
Висвітлено запити та потреби суспільства в сильному лідері авторитарного типу.
Розглянута різниця між іміджем демократичного та авторитарного лідера і їх специфіки формування. In this article “Forming the image of authoritarian leader in modern conditions” the
authors are trying to present inquires and needs of society in a strong leader of authoritarian type. In the article the difference between image of democratic and the authoritarian leader and the specific of their forming is describing. The article is prescribed to the experts who are interested in practical politology, teachers and students at the department of political sciences.